Analogy of silicon and boron in plant nutrition - Sheng, Huachun; Lei, Yuyan; Wei, Jing; Yang, Zhengming; Peng, Lianxin; Li, Wenbing; Liu, Yuan (Frontiers in Plant Science, 2024)
Silicon (Si) and boron (B) are a class of elements called metalloids, which have properties like metals and non-metals. Si is classified as a quasi-essential element, while B is a micronutrient element for plants. Nowadays, numerous discoveries have shown the analogy of silicon and boron in plant nutrition. In this minireview, the molecular mechanisms for the transport of these two metalloids are compared. We also discussed the chemical forms of Si and B and their functional similarity in response to environmental stresses in plants. In conclusion, it can be proposed that cell wall-bound silicon rather than silica might partially replace boron for plant growth, development, and stress responses, and the underlying mechanism is the Si contribution to B in its structural function.